Antidiabetic activity test of mangrove leaf extract (Rhizophora mucronata) from west lombok regency using the oral glucose tolerance test method - Amran Halim; Raisya Hasina; Lina Permatasari (Universitas Mataram, 2026)
Black mangrove (Rhizophora mucronata) is recognized as a natural ingredient with potential antidiabetic properties due to the presence of active compounds such as flavonoids, alkaloids, and tannins. Conventional antidiabetic drugs like metformin often cause side effects, highlighting the need for safer, natural alternatives. The safety of Rhizophora mucronata leaves has been demonstrated through acute toxicological studies. This study aimed to evaluate the antidiabetic activity of Rhizophora mucronata leaf ethanol extract and determine the most effective dose. Unlike previous studies that used maceration and methanol as solvent, this research employed a sonication method with 96% ethanol solvent and collected leaf samples from the Cemare area, West Lombok, to reflect local conditions. Twenty-five mice were divided into five groups: negative control (0.5% Na CMC), positive control (metformin 500 mg/kg body weight), and three test groups receiving extract doses of 62.5; 125; and 250 mg/kg body weight. The first blood sample was taken to measure fasting blood glucose, followed by induction with a 50% glucose solution, and another blood sample was taken after 30 minutes. Then, the test solutions were administered, and blood glucose levels were measured at 30, 45, 60, 90, and 120 minutes post-administration. Blood glucose data were analyzed using SPSS version 25 with One Way ANOVA, Post Hoc Tukey, and Paired Sample T-Test. The results showed that doses of 125 mg/kg and 250 mg/kg body weight significantly reduced blood glucose levels (p<0.05), identifying these as the optimal doses. These findings support the potential of Rhizophora mucronata as a safe, natural antidiabetic therapy.